Health Policy and Shared Decision Making in Emergency Care: A Research Agenda. (December 2016) - Maughan, Brandon C.; Meisel, Zachary F.; Venkatesh, Arjun K.; Lin, Michelle P.; Perry, Warren M.; Schuur, Jeremiah D.; Pines, Jesse M.; Kizzie‐Gillett, Constance L.; Vaughan, William; Grudzen, Corita R.
Abstract: Although the Patient Protection and Affordable Care Act and other laws have promoted the use of shared decision making (SDM) in recent years, few specific policies have addressed the opportunities and challenges of utilizing SDM in the emergency department (ED). Policies relating to physician payment, quality measurement, and medical–legal risks each present unique challenges to adoption of SDM in the ED. This article summarizes findings from a health policy breakout session of the 2016 Academic Emergency Medicine Consensus Conference "Shared Decision Making in the Emergency Department: Development of a Policy‐relevant, Patient‐centered Research Agenda." The objectives were to 1) describe federal and state policies that influence utilization or assessment of SDM; 2) identify policies and policy‐focused knowledge gaps that serve as barriers to adoption of ED SDM; and 3) to define a consensus‐based, policy‐focused research agenda to support adoption of SDM in emergency care.